Semi-synthesis and evaluation of anti-acetylcholinesterase activity of some baicalein derivatives - Huân, Trần Thế; Ngọc, Đoàn Đình; Sơn, Trần Thái (Hue University Journal of Science: Natural Science, 2020)
Baicalein is a potential flavonoid for acetylcholinesterase inhibitor research to treat Alzheimer's disease. Six baicalein derivatives have been semi-synthesized via esterification and amino alkylation reactions. The in vitro acetylcholinesterase inhibitory activity of these derivatives was evaluated with the Ellman method, and certain improvement in the activity of some derivatives is observed. The methyl ester derivative shows the highest activity with an IC50 value of 51.64 µM.